Hair cortisol moderates the association between obstetric complications and child wellbeing - Fuchs, Anna; Dittrich, Katja; Neukel, Corinne; Winter, Sibylle; Zietlow, Anna-Lena; Kluczniok, Dorothea; Herpertz, Sabine; Hindi Attar, Catherine; Möhler, Eva; Fydrich, Thomas; Bermpohl, Felix; Kaess, Michael; et al. (Psychoneuroendocrinology, 2020)
Obstetric complications (OC) may have implications for later health outcomes. However, there is a lack of research examining the association between OC and behavior problems or quality of life (HRQoL). We aimed to close this gap and further investigate functioning of the hypothalamus-pituitary-adrenal (HPA)-axis as a potential physiological vulnerability moderating the association between OC and behavior problems and HRQoL. We investigated 232 mothers and their five to 12-year-old children. Presence of OC during the pre-, peri-, and postnatal phases was determined by interviewing mothers. Children’s behavior problems (CBCL, TRF) and HRQoL (Kidscreen rated by mothers and children) were assessed. Children gave 3 cm strands of hair for analysis of hair cortisol (HC). Structural equation modeling analyses with a latent variable of child outcome (“distress”), OC as predictor and HC as a potential moderator were conducted. OC significantly predicted distress (β = .33, p < .01). The model showed a good fit to the data: χ2(14)=15.66, p < .33, CFI=.99, TLI=.99, RMSEA=.02, 90 %CI [.00, .06], SRMR=.04. In addition, HC moderated the association between OC and distress (β=-.32, p < .01). The moderation model also showed a good fit: χ2(14) =7.13, p = .93, CFI=1.00, TLI=1.06, RMSEA=.00, 90 %CI [.00, .02], SRMR=.03. Results indicated that the association between OC and distress was significant only when children had low HC-levels. This was also the case for both externalizing and internalizing behavior problems. Our results underline the notion of OC as a risk factor for child behavior problems and wellbeing and point to an important role of the children’s physiological set-up such as HPA-functioning.